Does Accession to the European Union Foster Competition Policy? Country-level Evidence - Michael Böheim; Klaus S. Friesenbichler (Austrian Institute of Economic Research (WIFO), 2014)
This paper argues that the accession to the European Union improves the quality of competition policy via the implementation of pro-competitive policies, especially antitrust and competition policies, embedded in the Community Acquis. We assess this conjecture empirically for the (former) transition economies of Central and Eastern Europe, using member countries as well as developing and developed countries in Europe and Central Asia as a control group. The data used is a macro-economic panel of 48 countries covering six 3-year periods between 1995 and 2012. We find that EU accession positively affected the quality of competition policies over and above an overall trend towards more market oriented policies. The improvement in competition policy was not reversed in a single country of the sample. The findings are robust when controlling for endogeneity issues. We also document a slow-down in policy reform efforts in the aftermath of the crisis, challenging previous literature which expects a reform enhancing effect of crisis.
Keywords: 330; competition policy; regulation; economic transition; Community Acquis; EU accession